The Role of School Management Teams in Developing an Inclusive Education Culture in Secondary Schools - Ali , Muhammad (UJoST- Universal Journal of Science and Technology, 2023)
This qualitative case study explores the role of school management teams (SMTs) in fostering an inclusive education culture at a public secondary school in Bekasi City, Indonesia. Through interviews, classroom observations, and document analysis, the study examines how SMTs plan, implement, and evaluate inclusive practices. Findings indicate that SMTs are pivotal in policy formulation, teacher capacity building, stakeholder collaboration, and resource mobilization. However, challenges such as limited infrastructure, inadequate teacher training, and societal stigma persist. The study concludes that effective leadership, strategic planning, and community engagement are essential for sustainable inclusive education.